Development of elite hurdlers: Assessment of the individual athlete - Raske Sparray, K.
About identifying and training elite hurdlers (14-17 years) in the USA. The first part explains the profile of an alite hurdle and tests to identify the talent. The second part describes the (long term) planning and organizing of training. Conclusion: The development of elite hurdlers requires approximately six to eight years of specialized training and an additional four years of general physical conditioning to reach top performance (Korchemny, 1996). Fifty per cent of the world's best 400m hurdlers are over 27 years old (Stepanov, 1989) and average age of the female world class 100m hurdler is between 24-30 years of age. With this in mind, the U.S. continually looks to the college coach to target this select group of upcoming hurdlers and develop them accordingly. The high school or club coach is responsible for the development during the ages of 14- 17. The idea of periodization in set- ting up a training program is a must for progress. A good coach will be able to train all athletes together early in their program with the focus on developing all the biomotor capabilities. Once prospective hurdlers are identified, an introduction and encouragement to the hurdle events is necessary. Special attention must be given to developing horizontal velocity, mechanical efficiency, mobility of the hip joint, and hurdle rhythm. Following sound sprint training and exercise selection principles, such as sequencing, is certain to be a critical asset to the training program and hence overall development. It should be noted that many coaches find it difficult to transfer the planning and organization of training to the actual practice. The actical application of any training theory relies on the ability of the coach to "unfold the art." The art of coaching takes into account common sense, intuition, and perceptions. Transferring theory into practice when planning the training program can be made easy with a training menu system or inventory. This piece of guidance can make a significant impact in any training program. Use of training inventories can better enable the coach to set up and follow the overall flow of an annual plan. Planning is essential to coaching since there is so much information needed to organize a training program. Inventories will be able to categorize each area, for you to then choose the appropriate exercises. As with any training program, there is a need to continually assess and monitor. A coach can do this through testing, biomechanical evaluation/film analysis; postural/alignment/joint stability checks; tactical and technical evaluations; specific endurance evaluation; and performances. Coaches should then make adjustments accordingly. It is advisable for the coach to experiment throughout the year to find the optimal means of eliciting peak performances at the proper time. It is important for the coach to record or write down as much information as possible in addition to the overall periodized plan. A coach should write a justification for each segment of the training plan, important observations at practices or at competitions, how the athletes respond to you, others, and training. Many work with dozens of athletes during a year and this assists the coach in retaining critical information for each individual. Developing the hurdler physically is just part of the challenge in coaching. Athletes in my program are developed from a holistic standpoint. The concept here is based on development of mind, body and soul together. Encouragement and support to become good citizens, successful students, and quality people is the first and foremost objective that any coach can be proud of.